2022
DOI: 10.3390/ijerph19042088
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Biallelic Mutations in ECHS1 in a Case with Short-Chain Enoyl-CoA Hydratase (SCEH) Deficiency-Case Report and Literature Review

Abstract: ECHS1 gene mutations are known to cause mitochondrial short-chain enoyl-CoA hydratase 1 deficiency, a neurodegenerative disorder characterized by psychomotor development delay, lactic acidosis, and basal ganglia lesions resembling Leigh syndrome. Short-chain enoyl-CoA hydratase 1 (ECHS1) deficiency is a very rare and new disorder, with a wide phenotypic spectrum and different outcomes ranging from neonatal death to survival into adulthood. Since the identification of ECHS1 deficiency in 2014, almost 63 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…1A >G (p.Met1? ), 3 the novel (p.Leu123Phe) change, 7 c.232G > T (p.Glu78Ter), 8 9 c.817A > G(p.Lys273Glu), 4 13 14 and c.394C > T (p.Ala132Thr) 17 were the other associated variations. However, till date the nonsense variation (chr10:g.133366045G > A) resulting in a stop codon that is identified in our patient has not yet been reported.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…1A >G (p.Met1? ), 3 the novel (p.Leu123Phe) change, 7 c.232G > T (p.Glu78Ter), 8 9 c.817A > G(p.Lys273Glu), 4 13 14 and c.394C > T (p.Ala132Thr) 17 were the other associated variations. However, till date the nonsense variation (chr10:g.133366045G > A) resulting in a stop codon that is identified in our patient has not yet been reported.…”
Section: Discussionmentioning
confidence: 93%
“…Korenke 14 described two unrelated girls, one with episodic opisthotonos and another with hemidystonia, both occurring in late afternoon after physical exertion. Muntean et al 4 described a girl with paroxysmal dystonia starting at 8 years of age. However, the combination of persistent dystonia with generalized choreoathetosis and alternating skew deviation with partial tonic OTR as in our case are hitherto unreported among patients with the milder phenotype, although choreoathetosis has been infrequently reported in patients with the Leigh-like syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical testing results were variable between reports. The most consistent biomarkers published were serum lactate, which was elevated in roughly 2/3 of the cases and 2‐methyl‐2,3‐dihydroxybutyrate, which was elevated in urine organic acid testing in approximately 1/3 of the patients (Bedoyan et al, 2017; Ferdinandusse et al, 2015; Fitzsimons et al, 2018; Haack et al, 2015; Marti‐Sanchez et al, 2020; Muntean et al, 2022; Peters et al, 2014; Yang & Yu, 2020). A recent study demonstrated differences in urine levels of some valine metabolites S‐(2‐carboxypropyl) cysteine/cysteamine, S‐(2‐carboxyethyl) cysteine/cysteamine between six patients and six controls (Kuwajima et al, 2021).…”
Section: Introductionmentioning
confidence: 91%
“…Among those with developmental delay, regression of skills was commonly reported (Carlston et al, 2018; Fitzsimons et al, 2018; Muntean et al, 2022; Tetreault et al, 2015; Yamada et al, 2015; Yang & Yu, 2020). Nystagmus and optic atrophy (Ferdinandusse et al, 2015; Fitzsimons et al, 2018; Haack et al, 2015; Huffnagel et al, 2018; Muntean et al, 2022; Peters et al, 2014; Sakai et al, 2015; Tetreault et al, 2015), dilated/hypertrophic cardiomyopathy (Ganetzky et al, 2016; Muntean et al, 2022; Peters et al, 2014), apneic spells (Bedoyan et al, 2017; Fitzsimons et al, 2018) were also reported albeit less frequently. Most of the reported patients had MRI findings of increased T2 and FLAIR signal in brainstem, basal ganglia and/or supratentorial white matter, regions characteristically involved in Leigh Syndrome (Balasubramaniam et al, 2017; Bedoyan et al, 2017; Carlston et al, 2018; Ferdinandusse et al, 2015; Fitzsimons et al, 2018; Haack et al, 2015; Huffnagel et al, 2018; Mahajan et al, 2017; Muntean et al, 2022; Olgiati et al, 2016; Peters et al, 2014; Sakai et al, 2015; Shayota et al, 2019; Tetreault et al, 2015; Uesugi et al, 2020; Yamada et al, 2015; Yang & Yu, 2020).…”
Section: Introductionmentioning
confidence: 99%